Effect of Marine Microalgae Biomass (Nannochloropsis gaditana and Thalassiosira sp.) on Germination and Vigor on Bean (Phaseolus vulgaris L.) Seeds “Higuera” - Brisia Lizbeth Puente-Padilla; Gabriel Ivan Romero-Villegas; Alberto Sánchez-Estrada; Luis Alberto Cira-Chávez; María I. Estrada-Alvarado (Life)
The production of marine microalgae provides a sustainable solution for agriculture, acting as biostimulants to enhance seed germination, vigor, and early growth. In the present work, the parameters of pH, airflow, and dilution speed were established to produce biomass of two species of marine algae (Nannochloropsis gaditana and Thalassiosira sp.); in addition, its capacity to stimulate the germination of bean seeds was evaluated. The experimental treatments included three biomass concentrations (Cb) of both microalgae species (0.5, 1, and 1.5 g·L−1) and a control (distilled water) at two temperatures (25 and 35 °C). The rate, index, average time, time at 50% germination, and vigor were evaluated. The results indicated that the highest yield of microalgae biomass was obtained with D = 0.3 day−1 for N. gaditana and 0.2 day−1 for Thalassiosira sp. Microalgae biomass showed activity as a biostimulant on germination, improving the germination rate and reducing the germination time with better vigor for the seedlings at each of the evaluated concentrations.